PENGARUH BAURAN PEMASARAN, KEPERCAYAAN KONSUMEN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN KONSUMEN SURVEI PADA JAMAAH UMRAH PT BARAKALLAH DUNIA WISATA - Rezky Muhamad Akbar (Jurnal Manajemen, 2018)
The aim of this study was to examine the impact of marketing management, Customer Trust, and Company Image that affected customer satisfaction in PT.Barakallah Dunia Wisata. Several previous studies that support marketing management, Customer Trust, and Company Image that affected customer satisfaction has been demonstrated. Therefore, the research design is causality.The population of this research is the customers of PT.Barakallah Dunia Wisata in Jakarta. The sample was 100 konsumen. Data used in this study of primary data through questionnaires. The sampling technique is non-probability sampling, namely convenience sampling. Analytical tools used are statistical multiple linear regression. The results of the analysis stated that impact of marketing management, customer trust and company image on consumer satisfaction and significant. Research results comes with a discussion of the strategic solution from the results of descriptive statistical analysis.